Graphical Instruction For Coloring Mobile-Based Augmented Reality Applications - Abdullah, Muhammad Colmann; Che Dalim, Che Samihah; Sunar, Mohd Shahrizal; A.Mohd Yunos, A.Rafidah (2016)
This paper describes an empirical study of effectiveness and satisfaction utility in augmented reality coloring application. Five children aged 6, 7 and 8 from several Primary School participated in usability test. This study involved applications that were used to study and observe the children interaction with augmented reality coloring application. These pre-tests were to measure the effectiveness and satisfaction on wizard Oz by conducting usability test, observation survey methods in order to assess children experience with augmented reality application. By following children computer interaction methodology the usability test appears to be helpful by providing input to design user interface and improve user experience. The result offers graphical instruction on interaction design framework for children augmented reality application. This research employed a qualitative experimental research with purpose to investigate the effects of user interface and user experience. This study had resulted animated graphical instruction in the production of coloring augmented reality application. It is a critical and comprehensive review of a range of recently published literature sources addressing various issues related to children computer interaction